Return on Assets, Return on Equity, and Net Profit Margin Affect Stock Prices in Indonesia: Return on Assets, Return on Equity, dan Net Profit Margin Berpengaruh Terhadap Harga Saham di Indonesia - Pawulandari, Aurelia; Nurasik, Nurasik (Indonesian Journal of Law and Economics Review, 2024)
Abstract: This study investigates the influence of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM) on stock prices within the context of the consumer goods manufacturing sector in Indonesia. The general background emphasizes the significance of financial indicators in shaping investor perceptions and market dynamics. The specific background reveals a gap in existing literature regarding the varying impacts of these financial metrics on stock prices, particularly in emerging markets. The aims this study investigates the correlations between ROA, ROE, NPM, and stock prices in 68 manufacturing companies listed on the IDX from 2019-2022 using a quantitative methodology. The results indicate that both ROA and ROE have a positive and significant impact on stock prices, highlighting the attractiveness of firms with higher asset and equity returns. Conversely, NPM exhibits a negative and significant effect on stock prices, suggesting that it reflects operational inefficiencies across various departments. The novelty of this study lies in its detailed examination of these relationships in an Indonesian context, contributing to a deeper understanding of how financial metrics influence investor behavior. The implications This research underscores the need for investors to exercise caution in their investment strategies, especially in light of potential financial reporting manipulations affecting firm value. Highlights: ROA and ROE positively affect stock prices, attracting investors. NPM negatively impacts stock prices, indicating inefficiencies. Results guide investor strategies and risk management decisions. Keywords: Return on Assets, Return on Equity, Net Profit Margin, Stock Prices, Investment Strategies